Computer simulation of the formation of hollow nanocrystals - Belova, Irina V.; Murch, Graeme E. (Diffusion Fundamentals, 2005)
Experiments on the formation of hollow nanocrystals of cobalt sulphide by way of the Kirkendall effect have been reported recently by Yin et al. We perform a set of Monte Carlo simulations of the process to explore the phenomenon.